Squeezed Out: Commercial Baby Food Pouch Feeding Practices, Caregiver Perceptions, Caries Experience, and Public Health Implications - Catherine Eshaghzadeh; Suzanne Kan; Ramon Sa-a; Chi-Hong Tseng; Yan Wang; Francisco Ramos-Gomez (Children, 2026)
Background/Objectives: Early childhood caries (ECC) is the most common chronic disease of childhood worldwide. Commercial baby food pouches have become increasingly popular because of their convenience and perceived healthfulness; however, their sugar content and characteristic feeding practices have raised concerns regarding children’s oral health. This study characterized caregiver-reported commercial baby food pouch use, feeding practices, caregiver perceptions, and caries experience while considering implications for child oral health and public health policy. Methods: A cross-sectional study was conducted among 200 caregiver–child dyads attending the UCLA Children’s Dental Center. Eligible children were aged 0–6 years and currently consumed commercial baby food pouches. Caregivers completed a structured survey assessing pouch use, feeding practices, brand preferences, and perceptions, and children underwent oral examinations to assess caries experience using the decayed, missing, and filled teeth (dmft) index. Results: One-third (34%) of children consumed at least one commercial baby food pouch daily, 32% consumed pouches several times per week, and 34% consumed them less than once per week. Pouch consumption frequency differed descriptively across age groups, with approximately one-third of children aged 0– 0.05). Two-thirds of caregivers (66%) reported providing pouches primarily during travel or transportation, and convenience was the most frequently cited caregiver-reported advantage. No statistically significant association was observed between caregiver education and pouch use frequency (χ2(20, N = 200) = 23.72, p = 0.26). The three most commonly reported pouch brands contained total sugar levels ranging from 95% to 162% of those found in a similarly sized serving of Coca-Cola, despite the pouch products reporting 0 g of added sugars on their Nutrition Facts labels. Conclusions: Among current pouch consumers, commercial baby food pouches were frequently incorporated into feeding practices throughout early childhood. The substantial total sugar content of commonly reported pouch products, caregiver feeding practices, and common perception as healthy products highlight opportunities for anticipatory guidance, caregiver education, clearer nutrition labeling, and public health policies that support healthier feeding practices.